Bridge to cancer therapy in patients with chronic heart failure: implantation of a left ventricular assist device before surgical treatment of gastric cancer - K. G. Ganaev; S. K. Kurbanov; E. E. Vlasova; E. V. Dzybinskaya; R. S. Latypov; K. V. Mershin; I. S. Stilidi; A. A. Shiryaev; R. S. Akchurin (Вестник трансплантологии и искусственных органов, 2024)
The co-occurrence of chronic heart failure (CHF) and cancer is becoming more and more common as people live longer. The lack of a structured approach to the treatment of cancer patients with severe cardiovascular conditions is an essential issue. Up to 25% of cancer patients cannot be operated on for their main disease profile due to the presence of cardiovascular disease. This article describes a clinical case of successful treatment of a patient with two competing (prognosis-determining) diseases: end-stage heart failure and stomach cancer within the framework of a bridge-to-cancer strategy.